Self-Care Behavior in Heart Failure Patients: Impact on Cardiovascular Health Profile - Dwi Prihatiningsih; Widaryati Widaryati (University of Muhammadiyah Malang, 2021)
Introduction: Heart failure is a complex syndrome with characteristic symptoms of shortness of breath, fatigue, and signs of fluid retention. Self-care is the cornerstone of successful heart failure management. The cardiovascular health profile is a direct indicator of successful self-care. Objectives: The objective of the study was to examine the association between self-care and the cardiovascular health profile including smoking status, body mass index, total cholesterol, blood pressure and blood glucose level. Methods: This study is a cross-sectional study of heart failure patients at PKU Muhammadiyah hospital of Yogyakarta between August to October 2020 with sample of 100 participants. Chi square test was used to test the relationship between the two variables. Results: The finding shows that self-care management is the dimension with the highest level of self-care (96.2%) and self-care confidence is the lowest percentage of adequate self-care (13.0%). Among five cardiovascular health profile, smoking status is the highest metric with an ideal percentage (95.0%) and the lowest percentage was blood glucose metric (14.0%). The results of the correlation test between self-care and the total cardiovascular health profile showed no significant relationship between the two variables. However, there was one dimension of self-care, namely self-care maintenance which has a significant relationship with total cholesterol levels with a value of p = 0.008. Conclusions: It is important to provide individualized health education to help the patients to improve their self-care and cardiovascular health profile in heart failure patients.